2018
DOI: 10.1016/j.heares.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Dimension-selective attention as a possible driver of dynamic, context-dependent re-weighting in speech processing

Abstract: The contribution of acoustic dimensions to an auditory percept is dynamically adjusted and reweighted based on prior experience about how informative these dimensions are across the long-term and short-term environment. This is especially evident in speech perception, where listeners differentially weight information across multiple acoustic dimensions, and use this information selectively to update expectations about future sounds. The dynamic and selective adjustment of how acoustic input dimensions contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 132 publications
11
53
0
Order By: Relevance
“…Another class of models which aim to explain the effects of language experience on dimensional weighting during categorization are dimension-selectiveattention accounts, which suggest that up-weighted dimensions are more salient, tending to capture selective attention and therefore influence categorization to a greater extent (Gordon et al 1993, Francis and Nusbaum 2002, Holt et al 2018. That language experience can have an effect on dimensional salience in speech is supported by the results of Experiment 3, which showed that Mandarin speakers continue to be greatly influenced by pitch information even when explicitly asked to direct their attention away from pitch and towards another dimension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another class of models which aim to explain the effects of language experience on dimensional weighting during categorization are dimension-selectiveattention accounts, which suggest that up-weighted dimensions are more salient, tending to capture selective attention and therefore influence categorization to a greater extent (Gordon et al 1993, Francis and Nusbaum 2002, Holt et al 2018. That language experience can have an effect on dimensional salience in speech is supported by the results of Experiment 3, which showed that Mandarin speakers continue to be greatly influenced by pitch information even when explicitly asked to direct their attention away from pitch and towards another dimension.…”
Section: Discussionmentioning
confidence: 99%
“…For example, according to these models, when native Mandarin speakers categorize English syllables as stressed or unstressed, they refer to tone categories in Mandarin, and so place more weight on pitch information (and less on other cues) compared to native English speakers, given that pitch is by far the most important dimension for distinguishing between lexical tones (although other cues such as duration can be used if pitch is neutralized, such as in whispered speech; Lin and Repp 1989, Blicher, Diehl & Cohen 1990, Whalen and Xu 1992, Fu and Zeng 2000, Liu and Samuel 2004. Attentional theories of how information from different acoustic dimensions is combined during speech perception suggest that dimensions that have a greater tendency to capture attention are more strongly weighted (Gordon, Eberhardt & Rueckl 1993, Francis and Nusbaum 2002, Holt et al 2018. According to these models, repeated task-relevance of a particular dimension leads to an increase in perceptual salience of that dimension, thereby increasing the weight that is assigned to that dimension as a source of evidence during perception.…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, perceptual weights are not fixed: dimensional weights shift when the fidelity of the signal is degraded (for review see Holt, Tierney, Guerra, Laffere, & Dick, 2018). For example, when speech is presented in masking noise, VOT is harder to detect, making F0 more effective at signaling voicing categories.…”
Section: Structural Redundancy In Speechmentioning
confidence: 99%
“…Despite the importance of robust auditory selective attention for everyday listening, there are large individual differences in the ability to listen and respond to single auditory streams in the presence of distractors (47). The neural foundations of individual differences in selective attention are however poorly understood, as previous studies of the neural correlates of selective attention have used small numbers of participants and focused their analyses on main effects of attention.…”
Section: Introductionmentioning
confidence: 99%